CONGENITAL CMV-INFECTION WITH SEVERE CLINICAL ISSUSES- A COMPELLING CASE REPORT IN NORTH MACEDONIA - Vejseli, Besim Murat; Mandzukova, Hristina; Timovska, Silvana Naunova; Kimovska, Mica; Sofijanova, Aspasija (Journal of Morphological Sciences, 2024)
Cytomegalovirus (CMV) is one of the most common congenital infections in the world and has a mild or asymptomatic course in immunocompetent patients. Nonetheless, in certain population groups, including newborns, who become infected in utero can have significant and, in many cases, even lethal consequences. However, congenital cytomegalovirus (CMV) is not yet well known in women of childbearing age. In this case, we present a newborn infant who presented with thrombocytopenia, petechiae, and direct hyperbilirubinemia because of infection with CMV. At first the diagnosis process pointed to congenital sepsis rather than CMV. The significance of including a TORCH panel in the assessment of atypical presentations in the newborn are manifested in this case. The process of punctual Diagnosis of CMV is of serious importance because untreated infections can lead to lifelong consequences, even death. Keywords: cytomegalovirus, congenital infection, newborn.